An Appraisal of Asia-Pacific Cities as Control and Command Centres Embedded in World City Network - Zeyun, Li; Sheikh Dawood, Sharifah Rohayah; Xiaoxiao, Zhang (Engineering, Technology and Applied Science Research (ETASR), 2017)
Since the globalization trend is proliferating at a staggering rate, world cities have emerged as the most dominant vanguard incorporated into global economy. Control and command function is one of the robust integral parts of world city formation, which is closely associated with the corporate headquarter status of some dominant multinational companies. Previous research works on this topic tend to concentrate on the Western Europe and North American arenas neglecting the Asia- Pacific region. Hence, the objective of this paper is to explore control and command functions of Asia-Pacific cities with reference to headquarters’ locations of multinational companies. The methodology will utilize the Forbes global 2000 dataset from the seminal study of GaWC research group, and apply the control and command center model and the interlocking city network model to discover the control and command index, as well as network connectivity of Asia-Pacific cities. Based upon the empirical study of this research, we could identify the hierarchical structure and spatial structure of Asia-Pacific world cities to emerge as some control and command centers embedded in world city network.